Genetic pathways underpinning hormonal stress responses in fish exposed to short- and long-term warm ocean temperatures. (January 2021) - Goikoetxea, Alexander; Sadoul, Bastien; Blondeau-Bidet, Eva; Aerts, Johan; Blanc, Marie-Odile; Parrinello, Hugues; Barrachina, Célia; Pratlong, Marine; Geffroy, Benjamin
Graphical abstract: Highlights: Small within-day increases in temperature are physiologically stressful. Whole-fish transcriptomic analysis revealed a signature of warming. Fish kept at high temperature accumulate more cortisol in scales than those kept at low temperature. We propose fish scales as a relevant indicator of global warming in wild populations. Abstract: Changes in ocean water temperature associated with global climate change are bound to enormously affect fish populations, with potential major economic consequences in the aquaculture and fisheries industries. A link between temperature fluctuations and changes in fish stress response is well established. In this study, we aimed to assess the effects of a short- (4 days) or a long-term (4 months) exposure to warm temperature in the stress physiology of European sea bass ( Dicentrarchus labrax ) larvae and juveniles. First, cortisol ( i.e. the main stress hormone in fishes) analysis was used to confirm that a steady and short-term elevation of temperature acts as a physiological stressful event in these fish, and cortisol release is indeed above a metabolic increase linked to temperature. Moreover, our results verified that measurement of cortisol released into the water can be reliably employed as a non-invasive indicator of acute thermal stress in experimental conditions. Secondly, the different effects on the genetic cascade underlying the stress response between long-term low or high thermal treatments were evaluated at two larval development stages via candidate-gene and whole-transcriptome approaches. Interestingly, opposite expression for some key stress genes ( nr3c1, nr3c2 and hsd11b2 ) were observed between developmental stages, highlighting the distinct adaptive mechanisms controlling the primary and secondary responses to a stressor. Surprising expression patterns for some understudied genes involved in the stress axis were also revealed, including crhr1, mc2r, mc5r, trh or trhr, which should be further explored. Finally, evaluation of cortisol content in scales was successfully used as a biomarker of chronic thermal stress, with 10x more cortisol in fish kept at 21 °C vs 16 °C after 4 months, supporting the gene expression results observed. The use of such a method as a proxy of long-term stress, unprecedented in the literature, holds a vast array of applications in further research, in particular, in the investigation of the impact of global warming on wild fish populations.